2011
DOI: 10.1111/j.1471-8847.2010.00292.x
|View full text |Cite
|
Sign up to set email alerts
|

BECAUSE WE CAN: CLASHES OF PERSPECTIVE OVER RESEARCHER OBLIGATION IN THE FAILED PrEP TRIALS

Abstract: This article examines the relationship between bioethics and the therapeutic standards in HIV prevention research in the developing world, focusing on the closure of the pre-exposure prophylaxis (PrEP) trials in the early 2000s. I situate the PrEP trials in the historical context of the vertical transmission debates of the 1990s, where there was protracted debate over the use of placebos despite the existence of a proven intervention. I then discuss the dramatic improvement in the clinical management of HIV an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…While such a provision is indicated internationally as a needed and socially just component of a standard of prevention in a biomedical HIV prevention trial, in certain contexts in Thailand, such as when Thailand-based research may be U.S. funded, the provision of injecting equipment may not be possible. It was explained that this was due to U.S. policy perspectives concerning certain forms of harm reduction such as the provision of clean injecting equipment [1]. This could result in a disjuncture between what the community believed should and could be provided within a trial context under local laws, and what researchers and trial sponsors were willing to offer based on their interpretations of these local laws and policies, combined with any pressures applied by international donors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While such a provision is indicated internationally as a needed and socially just component of a standard of prevention in a biomedical HIV prevention trial, in certain contexts in Thailand, such as when Thailand-based research may be U.S. funded, the provision of injecting equipment may not be possible. It was explained that this was due to U.S. policy perspectives concerning certain forms of harm reduction such as the provision of clean injecting equipment [1]. This could result in a disjuncture between what the community believed should and could be provided within a trial context under local laws, and what researchers and trial sponsors were willing to offer based on their interpretations of these local laws and policies, combined with any pressures applied by international donors.…”
Section: Resultsmentioning
confidence: 99%
“…These trials sought to test the efficacy of Tenofovir (Viread) as pre-exposure prophylaxis (PrEP) for HIV prevention in locations as diverse as Thailand, Cambodia, Malawi, Nigeria, Ghana and Cameroon [1]. The closure of these trials acted to prevent or in some cases slow the development of other biomedical HIV prevention trials in marginalized populations across these regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of randomized control trials have demonstrated clinical efficacy of PrEP [4][5][6][7][8][9][10][11] . However, early oral tenofovir trials among marginalized communities, including in Cambodia, Cameroon, Nigeria, and Malawi among female sex workers (FSWs) and in Thailand among people who inject drugs, drew international attention with concerns over ethical violations in research practices [12][13][14] . Organized community action led to a halt of the trials in Cambodia and Cameroon due to concerns about the standard of prevention and care 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Approximately ten years ago, international protests contributed to the early closure of two of the first placebo-controlled trials of antiretroviral pre-exposure prophylaxis (PrEP) – oral pills for preventing HIV infection in uninfected people (Editorial, 2004; Global Campaign for Microbicides, 2009; Grant et al, 2005; Haire, 2011; McGrory, Irvin, & Heise, 2009; Mills et al, 2005; Singh & Mills, 2005). One of these trials took place in Cameroon; the design was to enroll healthy adult women with multiple sex partners, including female sex workers, and to randomize these women to receive either placebos or antiretroviral pills intended to reduce the risk of acquiring HIV.…”
mentioning
confidence: 99%